Late-Onset Sjögren disease: A different clinical entity? - Cengiz, Celil Barlas; Kahraman Denizhan, Tuğba; Kaplan, Hüseyin; Oğuz Kökoğlu, Emel; Kızıltepe, Melih; Eren Cengiz, Burcu; Oğuz, Hanife; Şenel, Abdurrahman Soner (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2026)
Background and aim: Sjögren’s disease(SjD) exhibits heterogeneous clinical phenotypes influenced by age at onset. This study aimed to evaluate the impact of onset age on the clinical and serological characteristics of SjD in a Turkish cohort.Methods: We retrospectively analyzed 411 patients diagnosed with SjD between 2013 and 2024, fulfilling the 2002 AECG or 2016 ACR/EULAR criteria. Patients were classified as young-onset (60 years; EoSjD). Demographic, clinical, laboratory, and treatment characteristics were compared among groups.Results: The cohort comprised predominantly females (93.4%) with a median age of 55 years. RF positivity was significantly higher in EoSjS (35.5%) compared to YoSjD (27.9%) and AoSjD (19.2%, p=0.007). Inflammatory markers (ESR, CRP) were more frequently elevated in EoSjD. Interstitial lung disease (ILD) prevalence was highest in EoSjD (25.8%, p